Antagonistic profiling of volatile and non-volatile secondary metabolites produced by Trichoderma asperellum towards pathogenic Fusarium oxysporum f. sp. cicero - Popat Birari, Bhushan; Ingle, Sunil (Journal of Plant Protection Research, 2026)
Fungi of the genus Trichoderma are widely marketed as biocontrol agents against plant pathogens. However, some Trichoderma species may produce toxic secondary metabolites, underscoring the need for comprehensive safety assessments to ensure their ecological safety. In this study, the antifungal activities of volatile secondary metabolites (VSMs) and non-volatile secondary metabolites (nVSMs) produced by six Trichoderma asperellum strains (TaSrBh, TaSrYa, TaSrBu, TaSrUm, TaSrGa, and TaSrCh) were evaluated against the chickpea wilt pathogen Fusarium oxysporum f. sp. ciceri. Bioassays of VSMs and nVSMs revealed that TaSrGa and TaSrYa exhibited the strongest antifungal activity. The ethyl acetate extract of the TaSrYa strain showed excellent growth inhibition (60–100%) of F. oxysporum f. sp. ciceri, prompting further investigation into its metabolic profile. To identify potential fungicidal compounds, spectroscopic analyses were performed on the ethyl acetate extract of TaSrYa. The predominant compounds identified included 9-octadecenoic acid (26.32%), dehydroacetic acid (25.71%), 9-undecenal 2,10-dimethyl (11.31%), 7,10-octadecadienoic acid (8.62%), 9,12,15-octadecatrienoic acid 2,3-dihydroxypropyl ester (Z,Z,Z) (6.18%), and cis-Z-α-bisabolene epoxide (4.96%), which are likely responsible for inhibiting pathogen growth. Additionally, two-dimensional gas chromatography and spectroscopic analyses of volatiles from TaSrGa identified 67 VSMs, categorized as alcohols, alkanes, esters, acids, and terpenes. The examined T. asperellum strains demonstrated strong antagonistic effects against the pathogen responsible for chickpea wilt, suggesting that these biocontrol agents could be used in the formulation of natural fungicides, offering an eco-friendly alternative to synthetic fungicides.